Measurements and molecular interactions for N,N-dimethylformamide with ionic liquid mixed solvents - Attri, Pankaj; Reddy, P. Madhusudan; Venkatesu, P.; Kumar, Anil; Hofman, T. (Journal of Physical Chemistry B, 2010)
To understand the molecular interactions between N,N-dimethylformamide (DMF) with two families of ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (a) over the whole composition range at 25 degrees C under atmospheric pressure. The excess molar volume (V(E)) and the deviation in isentropic compressibilities (Delta K(s)) were predicted using these properties as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included two families of ILs such as ammonium salts and imidazolium salts. Diethylammonium acetate ([Et(2)NH][CH(3)COO], DEAA), triethylammonium actetate ([Et(3)NH][CH(3)COO], TEAA), triethylammonium dihydogen phosphate ([Et(3)NH][H(2)PO(4)], TEAP), and triethylammonium sulfate ([Et(3)NH][HSO(4)], TEAS) are ammonium salts and l-benzy1-3-methylimidazolium chloride (Bmiml[Cl]) belongs to the imidazolium family. The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion dipole, ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Temperature effect on the molecular interactions between ammonium ionic liquids and N,N-dimethylformamide - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Journal of Physical Chemistry B, 2010)
In view of the wide scope of molecular interactions between the highly polar compound of N,N-dimethylformamide (DMF) and ammonium ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (u) over the whole composition range at temperatures ranging from 25 to 50 degrees C under atmospheric pressure. To gain some insight into the several aggregations of molecular interactions present in these mixed solvents, we predicted the excess molar volume (V(E)) and the deviations in isentropic compressibilities (Delta K(s)) as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included the hydroxide series of ammonium ILs of tetramethylammonium hydroxide [(CH(3))(4)N][OH] (TMAH), tetraethylammonium hydroxide [(C(2)H(5))(4)N][OH] (TEAH), and tetrapropylammonium hydroxide [(C(2)H(7))(4)N][OH] (TPAH). The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion-dipole and ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.

Activity and stability of alpha-chymotrypsin in biocompatible ionic liquids: enzyme refolding by triethyl ammonium acetate - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
In view the of wide scope of structural information of biomolecules in biocompatible ionic liquids (ILs) in various applications including chemical and biochemical, it is essential to study the productive preferential interactions between biological macromolecules and biocompatible ILs. We have therefore explored the stability and activity of alpha-chymotrypsin (CT) in the presence of five ILs from different families, such as triethyl ammonium acetate (TEAA), triethyl ammonium phosphate (TEAP) from ammonium salts, 1-benzyl-3-methylimidazolium chloride ([Bzmim][Cl]), 1-benzyl-3-methylimidazolium tetrafluoroborate ([Bzmim][BF(4)]) from imidazolium salts and tetra-butyl phosphonium bromide (TBPBr) from phosphonium families. Circular dichroism (CD) and UV-vis spectrophotometer experiments were used to study CT stabilization by ILs, related to the associated structural changes and enzyme activity studies, respectively. We observed that all ILs have a dominant contribution to the stabilization of CT. The stability and activity of CT depends on the structural arrangement of the ions of ILs. Our experimental results explicitly elucidate that more hydrophobic imidazolium and phosphonium cations carrying longer alkyl chains of ILs ([Bzmim][Cl], [Bzmim][BF(4)] and TBPBr) were weak stabilizers for CT, while small alkyl chain molecules of triethyl ammonium salts (TEAA and TEAP) are strong stabilizers and therefore more biocompatible for CT stability. Our CD and NMR measurements reveal that TEAA is a refolding additive for CT from a quenched thermal unfolded enzyme structure.

Protic ionic liquid attenuates the deleterious actions of urea on alpha-chymotrypsin - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil; Byrne, Nolene (Physical Chemistry Chemical Physics, 2011)
We present a biocompatible ionic liquid, triethyl ammonium acetate (TEAA), that attenuates the denaturation action of a non-ionic chaotrope, urea, on the industrially relevant proteolytic enzyme alpha-chymotrypsin.

Water and a protic ionic liquid acted as refolding additives for chemically denatured enzymes - Attri, Pankaj; Venkatesu, P.; Kumar, Anil (Organic & Biomolecular Chemistry, 2012)
In this communication, we present the ability of water and a protic ionic liquid, triethyl ammonium phosphate (TEAP) to act as refolding additives for the urea-induced chemical denaturated state of the two enzymes, alpha-chymotrypsin and succinylated Con A. We show that the enzymatic activity is regained and in certain circumstances enhanced.